The Referral Phenomenon in the Functional Grammar of the Arabic Language: Applied Study in Surah Ya-sin [In Arabic] - Benayache, Nadjib (Milev Journal of Research and Studies, 2022)
This article deals with the topic of the referential phenomenon in fictional grammar, as it is the most important component of the modern linguistics lesson and a necessary element to determine the consistency, harmony and coherence of the text in a functional way. The author started by defining the referral phenomenon, explaining its importance and function, defining its patterns and tools.Then, he applied the referral functions to Surat "Ya-Sin". If this phenomenon appears to be a crucial element in the development of modern Arabic language lessons, then it should be studied and given the value it deserves.